Innovative Strategies of Tertiary Music Teachers in Teaching Musically-Challenged Students - Mabini, Jay P. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
This study focuses on the innovative strategies that tertiary music teachers (specialist music teachers and experts) employ to help musically-challenged students. Those who have trouble with rhythm, tonal acuity, music theory, and musical aptitude are operationally referred to as musically-challenged. Ten participants were selected through purposive sampling and responded to the interview questions using an interview guide. Thematic analysis was conducted on their responses to generate codes and themes in this investigation. This is a single case study that draws from constructivist and behaviourist learning theories. To help students who have difficulty with music, music and its related components should be valued as an essential part of the curriculum. Devoted teachers should authentically demonstrate all of the subject's contents using innovative teaching strategies, allowing students to immediately grasp the values to be inspired and confident in the subject. As a result, strategies such as identifying the weaknesses of the learners, informal instruction, collaborative learning, repetition, positive reinforcement in learning, technology integration, and patience have proven to be effective solutions to the case being studied.